Building microservices with Spring : using Spring cloud to build and deploy microservices within a distributed system - Bowersox, Kevin; Safari eBooks ([Place of publication not identified] : O'Reilly, 2017)
"Spring expert Kevin Bowersox offers a clear and practical path to building and deploying microservices in this detailed look at the Spring software components used to create those systems. This is a hands-on course designed for intermediate level Java developers. You'll review the meaning of microservice architecture and distributed systems; learn the basics of using Spring Boot and Spring Cloud; learn to use the Spring-based toolsets for service discovery, service registry, routing, load balancing, and fault tolerance; see how Spring Cloud makes it easier to access Netflix components; and build a small scale microservices project of your own."--Resource description page.
Presenter, Kevin Bowersox.
Title from title screen (viewed February 22, 2017).
Date of publication from resource description page.
Keywords: Application software -- Development; Java (Computer program language); Spring (Software framework); Distributed operating systems (Computers); Computer architecture; Cloud computing; Electronic books